The Territorial Penetration, Control, and Governance Nexus - Zdeněk Ludvík (Estudos Internacionais)
This paper explores the relationship between territorial penetration, control, and governance of violent non-state actors (VNSAs). The three concepts have been previously studied in isolation. However, this paper aims to fill a gap in the literature by linking them into a common framework. The article establishes a causal link between three concepts using the process tracing method within three instrumental case studies of radical religious VNSAs: Al-Qaeda in the Islamic Maghreb (AQIM), the Islamic State (Daesh), and Hezbollah. Within a given research framework, the analysis also identifies specific intervening phenomena and contextual factors that may have a causal influence on the nexus under study. The main source of primary data comprises open expert interviews conducted by the author. The article presents evidence that advanced non-state governance requires a sequence of sufficient material actor power (penetration, control), inclusive ideational power (ideology), and positive contextual influence. Only such a sequence of establishing VNSAs in the territory fulfils a necessary and sufficient condition for positively impacting their power and status.